2015
DOI: 10.1016/j.devcel.2015.08.006
|View full text |Cite
|
Sign up to set email alerts
|

BNIP-H Recruits the Cholinergic Machinery to Neurite Terminals to Promote Acetylcholine Signaling and Neuritogenesis

Abstract: Synthesis and release of neurotransmitters such as acetylcholine (ACh) are key to synaptic function. However, little is known about the spatial regulation of their synthesizing machinery. Here, we demonstrate that ataxia-related protein BNIP-H/Caytaxin links kinesin-1 (KLC1) to ATP citrate lyase (ACL), a key enzyme for ACh synthesis, and transports it toward neurite terminals. There, BNIP-H/ACL complex synergistically recruits another enzyme choline acetyltransferase (ChAT), leading to enhanced secretion of AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…In contrast, we noted decrease of ATCAY/BNIP-H (Fig. S4 C and D), an ataxia-related brain-specific scaffold protein, which was recently found to recruit choline acetyltransferase (ChAT) to neurite terminals, and promote cholinergic signaling (45,46). Furthermore, within 4 d following Dox administration, dTg-211 mice presented fourfold increases in the forebrain levels of miR-134 (Fig.…”
Section: Mir-211 Declinementioning
confidence: 77%
See 1 more Smart Citation
“…In contrast, we noted decrease of ATCAY/BNIP-H (Fig. S4 C and D), an ataxia-related brain-specific scaffold protein, which was recently found to recruit choline acetyltransferase (ChAT) to neurite terminals, and promote cholinergic signaling (45,46). Furthermore, within 4 d following Dox administration, dTg-211 mice presented fourfold increases in the forebrain levels of miR-134 (Fig.…”
Section: Mir-211 Declinementioning
confidence: 77%
“…That we did not observe a parallel change in the sequencing experiment may reflect mRNA editing of this gene's transcripts (15), and for which alignment of sequencing reads is sensitive. We also observed elevation of the ataxia-related scaffold protein ATCAY/ BNIP-H gene, which affects shuttling of the ACh synthesizing enzyme ChAT to neurite terminals (45,46), and mutations in which associate with variable psychomotor retardation phenotypes and cerebellar dysfunction, together indicating multileveled exacerbation of cholinergic signaling.…”
Section: Discussionmentioning
confidence: 94%
“…In addition to the lack of associated genetic variants or transcript expression changes in ATCAY, no histologic lesions supportive of neurodegeneration were identified within the central nervous system of Atcay ji-hes mice. It is likely that the phenotypic changes in the hesitant mouse are due to subcellular changes of neurite growth within the cerebellum [17,36,37]. Prevention of the hesitant phenotype was attempted through vitE supplementation but was unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…The inability of vitE supplementation to improve the phenotype of Atcay hes/hes mice provides indirect support that caytaxin does not bind vitE [12] and that ATCAY is not related to the eNAD/EDM phenotype. It has been proposed that neuronal changes within the Atcay ji-hes mouse are subcellular, altering cholinergic machinery axonal transport without causing neuronal degradation [36]. Additional work has also shown that caytaxin binds to kinesin lite chain for transport of ATP citrate lyase towards neurite terminals, leaving no room for binding of vitE [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation